2021
DOI: 10.1080/23311975.2021.1878978
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corporate social responsibility on SMEs’ performance in emerging market

Abstract: Corporate social responsibility (CSR) is a growing issue in emerging markets. This study aims to evaluate the impact of CSR on firms' performance by exploring the role of mediating variables such as corporate reputation (CR) and customers' purchasing intention (CPI). We use the quantitative technique of Partial Least Squares Structural Equation Modeling (PLS-SEM) techniques to analyze the data of the small and medium-size enterprises (SMEs) from the Southern Vietnam in 2020. The findings suggest a positive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Another study on Portuguese SMEs found the key benefits of social responsibility practices: better reputation with suppliers, consumers, and partners, enhanced employee motivation, improved quality, and enhanced productivity (Santos, 2011). A recent study supporting the present analysis's findings suggests a positive and significant effect of CSR on firms' performance through mediating the role of corporate reputation and consumer purchase intentions (Tiep et al, 2021). A study in Romania found that whether the firm follows a formal CSR action or not, they wish to do fair business at their best as a CSR.…”
Section: Discussionsupporting
confidence: 78%
“…Another study on Portuguese SMEs found the key benefits of social responsibility practices: better reputation with suppliers, consumers, and partners, enhanced employee motivation, improved quality, and enhanced productivity (Santos, 2011). A recent study supporting the present analysis's findings suggests a positive and significant effect of CSR on firms' performance through mediating the role of corporate reputation and consumer purchase intentions (Tiep et al, 2021). A study in Romania found that whether the firm follows a formal CSR action or not, they wish to do fair business at their best as a CSR.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, the COVID-19 emergency had resulted in a diminishing performance of employees in the front-line industry, potentially affecting the psychological well-being of hotel representatives as well. 68 The research has fortified the relationship between COVID-19 fear and employee job performance while finding that job insecurity changes may be a crucial mediating factor in understanding the severity of COVID-19ʹs impact.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“… [ 70 ] Effects of CSR on SMEs' performance in emerging market This study explores the mediating effects of corporate reputation (CR) and customers' purchasing intentions (CPI) on the relationship between CSR and businesses' performance (CPI). [ 71 ] The impact of CSR disclosure and board characteristics on corporate performance The study examine how board attributes like board independence, board size, and gender diversity affect company performance. It will also look into the effects of CSR disclosure.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…According to market-based law, an industry's competition structure predicts firms' CSR strategic choices [ 71 , 99 ]. Depending on their competitive background, firms can play a market-distinction role [ 70 ].…”
Section: Conceptual Frameworkmentioning
confidence: 99%